Ochratoxin-A incidence in different coffee (Coffea arabica L.) berry fractions - Chalfoun, Sára Maria; Batista, Luís Roberto (Coffee Science - ISSN 1984-3909, 2007)
Ochratoxin A (OTA) occurrence was studied in different coffee (Coffea arabica L.) berry types according to the processing method (dry or wet). Two hundred eighty nine coffee samples from 11 locations in the south of Minas Gerais State, Brazil were collected and analyzed. The sample types were overripe (35), cherry (4), cherry + green (11), husked cherry (18), cherry (parchment) (2), mixes ( boia - overripe berries dried on tree (97), varrição - coffee berries swept from ground (106) and green - not mature (12). In 128 samples (44,29%) OTA contamination was not detected but in 89 (30,80%), it was detected from 0,1 to 5,0 μg/kg. This results show that 75,09% of the analyzed samples would be within the limits in study by the European Commission that regulates OTA levels on coffee beans. Most cherry, cherry parchment, husked, green and coco (dried cherry) sample types had OTA contamination level bellow 5 μg/kg but in those from varrição ,only 22,64% were OTA negative, and 77,36% positive, with two samples with levels above 100 μg/kg. The varrição coffee that is already a type which gives low quality coffee beverage, also represents risk for coffee safety due to OTA presence as showed in this study. As for the toxigenic potential of the identified species associated with coffee beans, it was observed a higher frequency of OTA producer isolates at the Circumdati Section, mainly the fungus Aspergillus ochraceus G. Wilh, present in 95% of OTA positive isolates.